PERILAKU CARING PERAWAT DALAM MENINGKATKAN KECEMASAN PASIEN PRE OP DI GEDUNG PANCASILA LANTAI 1 RUMAH SAKIT AL HUDA GENTENG BANYUWANGI - Fany Anitarini; Anita Dwi Ariyani; Eka Afryliana (Journal of Nursing Care and Biomolecular, 2023)
Introduction: Anxiety is a response given by individuals to a threat in health services,which is characterized by feelings of fear and anxiety and describes feelings ofdoubt, helplessness, tension and worry. This can be caused by nurses not givingorientation to patients when entering the treatment room. The procedures andconsequences of hospitalization can all make the patient experience tension andanxiety. The purpose of the study was to determine the relationship between nurses'caring behavior and the patient's level of anxiety in the Pancasila Building 1st, AlHuda Genteng Hospital, Banyuwangi in 2021. Method: The research design used was correlation with cross sectional design. The population in this study were all patients in the Pancasila Building 1 Al Huda Genteng Hospital, as many as 80 people and the sample size was 67 respondents, using purposive sampling technique. Data were collected using a PCBquestionnaire for caring behavior and HARS for anxiety. The data obtained werethen coded, scored, tabulated, and analyzed by the Spearman rank test. Result and analysis: The results showed that most of the respondents with high category ofcaring behavior were 38 respondents (56.7%) and almost half of the respondentswith moderate level of anxiety were 22 respondents (32.8%). The results ofcalculations with the Spearman rank test obtained = 0.000. Because < 0.05, itmeans that there is an influence of nurse caring behavior on the patient's level ofanxiety in the Pancasila Building 1st, Al Huda Genteng Hospital, Banyuwangi in2021, with the correlation value (r) in the strong category of 0.729 in the negativedirection. Discussion : Seeing the results of this study, nurses were able to motivate respondents in the healing process by ignoring the factors that trigger anxiety levels. Keywords: caring behavior, anxiety